1997
DOI: 10.1046/j.1365-3083.1997.d01-366.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Immunity: an Additional Player in the Mosaic of Autoimmunity

Abstract: Autoimmune diseases are associated with a variety of predisposing factors. However, the relative contribution of each remains to be established. The purpose of the paper is to focus on cigarette smoking, a common Western habit, as a possible environmental factor for the emergence of autoimmunity. This association is described in view of several recent studies documenting increased susceptibility to autoimmune diseases among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 32 publications
(43 reference statements)
2
37
0
2
Order By: Relevance
“…Fung et al also found that smoking was related to PPTD (24); others, however, did not find smoking related to PPTD or autoimmune hypothyroidism (21,25 relation are: the possible dose-response effect that we found, the noxious effect of diverse components of tobacco on the thyroid and the effect of smoking on the immune system (26,27). This is the first study describing breast feeding as an independent protecting factor: women not breast feeding had a RR ¼ 11.1 for developing PPTD.…”
Section: Discussionmentioning
confidence: 47%
“…Fung et al also found that smoking was related to PPTD (24); others, however, did not find smoking related to PPTD or autoimmune hypothyroidism (21,25 relation are: the possible dose-response effect that we found, the noxious effect of diverse components of tobacco on the thyroid and the effect of smoking on the immune system (26,27). This is the first study describing breast feeding as an independent protecting factor: women not breast feeding had a RR ¼ 11.1 for developing PPTD.…”
Section: Discussionmentioning
confidence: 47%
“…[20][21][22][23][24][25] Cigarette smoking has been linked with increased disease activity in SLE. 26 Cigarette smoking has been suspected to increase the risk and the activity of SLE 20,32 and CLE.…”
Section: Discussionmentioning
confidence: 99%
“…25,[27][28][29] There is an association between cigarette smoking and autoimmune disease, including DLE. [20][21][22][23][24][25] The prevalence of smoking in patients with DLE was found to be 82%, vs. 22% in controls matched for age and gender. 23 About 84.2% of discoid patients with DLE are smokers vs. 33.5% of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 George et al observaram diminuição na atividade dos linfócitos T supressores em fumantes em comparação ã de não fumantes. 16 A gené-tica, portanto, determinaria quais reações imunes seriam desencadeadas pelo cigarro. 17 Freemer cigarros durante toda a vida.…”
Section: Discussionunclassified